KYRGYZSTAN’S SECURITY PROBLEMS TODAY - ABDUVALIEVA, Ryskul (CENTRAL ASIA AND THE CAUCASUS, 2009)
Regional stability and security consist of two levels—the external security of each country at the regional level and the internal security of each of them individually. A state’s external and internal security are closely interrelated concepts.It stands to reason that ensuring internal security and stability is the primary and most important task. But the external aspect also requires attention. This article takes a look at the most important problems of ensuring Kyrgyzstan’s security. The economic aspect occupies a central place in the academic discussions about national security. The keen attention to this problem is primarily provoked by the fact that a country’s security hinges on the state of its economy.Kyrgyzstan is a country with a low level of economic development. During the Soviet era it depended wholly on the economy of the entire country. The budget was replenished from the common union fund, a practice that could not continue after the state acquired its independence.The young state did not have enough funds and the necessary resources to meet its own needs. The breakdown in economic ties after the collapse of the Soviet Union generated negative changes in the economy, although internal reasons, such as the hastily and thoughtlessly conducted economic policy, de-centralization and privatization of state property in particular, wreaked greater havoc in the context of the economic crisis. Trade, industrial, and transportation enterprises were sold and resold in a short period of time to private organizations. The thriftless and careless attitude led to enterprises with immense economic possibilities and potential being broken down, parceled out, and essentially destroyed. Business management and free price formation, the functioning of a new fiscal and monetary system, and the development of new foreign economic relations have met with immense difficulties. Economic crisis is a consistent and legitimate phenomenon that inevitably occurs when the old order collapses and a new one is created.Economic crisis usually leads to a cutback in the budget, an increase in non-payments, and a drop in the standard of living.1 The economic reforms being carried out in the country did not yield the desired results. The world economic crisis, which the post-Soviet countries are also enduring, cannot help but have an effect on the situation in Kyrgyzstan. Today, solving the republic’s most important task—ongoing economic reforms—is accompanied by accumulation of the external debt, which is creating a dangerous trend that is leading to an increase in poverty.